Business data communications and networking - FitzGerald, Jerry 1936-; Dennis, Alan; Durcikova, Alexandra (Wiley, 2021)
"This chapter introduces the basic concepts of data communications. It describes why it is important to study data communications, how data communications fit within the discipline of Management Information Systems (MIS), and introduces you to the three fundamental questions that this book answers. Next, it discusses the basic types and components of a data communications network. Also, it examines the importance of a network model based on layers. Finally, it describes the three key trends in the future of networking."